Critérios de progressão para o ciclo de alfabetização: a necessary discussion - Almeida, Patrícia Rodrigues de; Jung, Hildegard Susana (Revista Hipótese, 2021)
The study seeks to reflect on the basic criteria for assessing literacy, including in the context of inclusion children. The method is of a qualitative nature, presenting an account of teaching experience with a group of children from the 3rd year of elementary school in a public school in the metropolitan region of Porto Alegre during the academic year of 2019. The importance of establishing propositional criteria, in line with the school's proposals and current legislation. Among these, we can mention: belonging, access, learning, continuity, singularity and complexity. Everyone can learn, each in their own time.
Keywords: Basic education; Literacy assessment; Literacy cycle